Can the elite slalom kayaker's performance be correlated with anthropometric, nutritional, genetic, psychological as sleep traits? - Leonardo Henrique Dalcheco Messias; Homero Gustavo Ferrari; João Bosco Pesquero; Marciane Milanski; Andrea Maculano Esteves; Marta Fuentes Rojas; Andressa Reginato; Kelly Cristina Malavazi-Piza; Elton Dias Silva; Fúlvia B. Manchado-Gobatto (Universidade Estadual Paulista (UNESP), 2018)
Abstract AIMS The aims of this study were to investigate and characterize the anthropometric, nutritional, genetic, psychological and sleep variables of slalom kayakers, and to verify the correlation of these variables with the slalom kayakers' performance. METHODS Ten elite Brazilian team slalom kayakers participated of this study. Nutritional analysis was made by the Food Record (three days), 24 Hour Dietary Recall and Food Frequency Questionnaire. The ACE I/D, AGTMet235Thr, ACTN3R577X and BDKRB2+9/-9 were genotyped for genetic profile. The Profile of Mood States (POMS) and Sports Competition Anxiety Test (SCAT) were applied to investigate the psychological variables. The Pittsburgh Sleep Quality Index (PSQI), Epworth Sleep Scale (ESS) and Morningness-eveningness questionnaire (MEQ) were used for sleep traits analysis. Performance trials were performed on a white-water course with 24 gates, and finish time was considered as the variable related to performance. RESULTS Significant correlations were obtained between Performance Time Trial and %Fat (r=0.77), Energy (r=-0.75), Protein (r=-0.76), Carbohydrate (r=-0.72), Vitamin B6 (r=-0.87), Vitamin A (r=-0.82), Thiamine (r=-0.77), Riboflavin (r=-0.71), Magnesium (r=-0.86) and Phosphorus (r=-0.74) intake, besides the Fatigue mood domain (r=0.73) and the SCAT score (r=0.67). Athletes genotyped with the I, T, R and +9 alelle also presented better performances. CONCLUSIONSIn summary, the novel results provided by this study reinforce the necessity of considering several aspects during athlete development in order to achieve better performance in competitions.